Rituximab treatment in Chinese patients with primary angiitis of the central nervous system - Wei, Yu-Zhen; Wang, Hua-Bing; Yin, Lin-Lin; Guo, Ai; Zhang, Lu-lin; Sun, Jia-Li; Lu, Ping; Zhang, Xing-Hu; Tian, De-Cai (Frontiers in Neurology, 2025)
ObjectivesTo assess the efficacy and safety of rituximab (RTX) in Chinese patients with primary angiitis of the central nervous system (PACNS).MethodsHerein, we present the outcomes of 8 patients who received RTX for PACNS. Seven patients underwent a brain biopsy showing vasculitis, while the remaining patient had a digital subtraction angiogram and clinical findings highly suggestive of vasculitis. Clinical evaluation, laboratory tests, and imaging modalities were performed during the initial RTX administration and follow-up. The Expanded Disability Status Scale (EDSS) disability score was used to assess treatment response and degree of disability.ResultsThe median age at diagnosis of the 8 patients (2 females) was 37.0 years. All patients had active disease when RTX treatment was initiated. Five of the eight patients had refractory disease, and received one or more conventional immunosuppressants (IS). Three patients had contraindications or refused conventional IS. Patients were followed up until their death or the final follow-up visit (median 18 months; range: 0–40 months). The median EDSS score at the last visit (median 3.0; range 0–9.5) was lower than before RTX administration (median 6.5; range 1.5–9.5). In 6 patients, RTX administration was associated with a marked reduction in the number of flare-ups. Two of the six patients developed infections: one with pneumonia, and the other with tuberculosis. In one patient, parenchymal gadolinium enhancement persisted, and a new lesion was found following three courses of RTX.ConclusionOur data suggest that RTX therapy may be an additional treatment option for Chinese patients with PACNS.